Politik Klientelisme Baru dan Dilema Demokratisasi di Indonesia - Hasrul Hanif (Faculty of Social and Political Sciences, Universitas Gadjah Mada, 2009)
Political clientelism remains political dilemma in South East Asian Politics, including Indonesian. Thus, democratization agendas in Indonesia Post Soeharto definitely should lead to transform political clientelism into more democratic political practices that based on citizenship. However, the experience of Prosperous Justice Party in enhancing party-based philanthropy activities in Yogyakarta shows that political clientelism did not fade away, but have been transformed into new type of clientelism which is more plural. The clients has grown into more autonomous but segmented. 771% paper concludes that the pattern of clientelism in contemporay Indonesinn politics has been changed from dependent and dominant relations into asymmetrical and reciprocal political transaction between more plural patrons and relatively autonomous clients.